2015
DOI: 10.1016/j.rbmo.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

M2/ANXA5 haplotype as a predisposition factor in Malay women and couples experiencing recurrent spontaneous abortion: a pilot study

Abstract: Recurrent spontaneous abortion (RSA) is a prevalent condition among the Malay population of Malaysia, where carriage risk of conventional hereditary thrombophilia factors has been generally ruled out. The contribution of M2/ANXA5, a common haplotype in the annexin A5 gene promoter, was evalauted for RSA in Malay. Seventy-seven women who had experienced two or more unexplained RSA and 41 available male partners were selected for study, with 360 population controls recruited from healthy Malay individuals. Incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The timing of clinical pregnancy loss is consistent with the previously reported time of loss in natural pregnancies with ANXA5 M2 carriers with RPL (Bogdanova et al, 2007, Tiscia et al, 2009, Miyamura et al, 2011, Tüttelmann et al, 2013, Hock et al, 2015, Demetriou et al, 2015). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The timing of clinical pregnancy loss is consistent with the previously reported time of loss in natural pregnancies with ANXA5 M2 carriers with RPL (Bogdanova et al, 2007, Tiscia et al, 2009, Miyamura et al, 2011, Tüttelmann et al, 2013, Hock et al, 2015, Demetriou et al, 2015). …”
Section: Discussionsupporting
confidence: 89%
“…The annexin A5 M2 haplotype (ANXA5 M2) is associated with reduced expression of ANXA5 in placentas from M2 haplotype carriers presenting with PE and FGR (Ota et al, 2013, Chinni et al, 2009, Markoff et al, 2010). Further, the M2 haplotype is associated with an increased risk of PMPCs: recurrent pregnancy loss (RPL) (Bogdanova et al, 2007, Tiscia et al, 2009, Miyamura et al, 2011, Rogenhofer et al, 2012, Tüttelmann et al, 2013, Hock et al, 2015, Demetriou et al, 2015), FGR (Tiscia et al, 2009) small for gestational age infants (Tiscia et al, 2012), and gestational hypertension (Tiscia et al, 2009). The haplotype is transmitted equally by males and females (Ota et al, 2013, Chinni et al, 2009, Markoff et al, 2010, Rogenhofer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Since M2/ANXA5 is linked with reduced expression of ANXA5 in chorionic placenta, 10,11 the associated comparable risks of male carriers in RPL couples may indicate impaired embryonic anticoagulant function. 5,12,14 This is in accordance with the well-studied role of ANXA5 as placental anticoagulant, enriched on the surface of chorionic syncytiotrophoblasts. 1…”
Section: Introductionsupporting
confidence: 83%
“…8 Reduction in ANXA5 messenger RNA abundance was demonstrated in chorion-carrying M2, 9 which was confirmed to be haplotype specific, 10 and concomitant decrease in ANXA5 protein levels has been detected in placental tissue of M2 carriers with a thrombophilic placental complication. 11 Differential enrichment of the haplotype has been observed in RPL patient-groups, contributing to relative risks for carriers from 1.5 to 2, compared to random population controls of German, 5,8 Bulgarian, 5 and Malaysian 12 ethnic backgrounds. Estimated relative risks in M2 carriers in relation to healthy control patients with negative history for infertility or miscarriage are between 1.8 and 3, depending on the number of miscarriages and categories of recurrent spontaneous abortion and embryonic development in patient cohorts of German, 5,8 Italian, 4 Bulgarian, 5 and Japanese 13 extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The M2 haplotype prevalence determined for the controls in this study and in the report by Cao et al is concordant with the estimations for the respective population-based samples (1000G project: CEU, Europeans 12.4%; CHB, Chinese, 16.0%) and with the frequency established for healthy cohort subjects from Nijmegen, Netherlands (11%) [ 30 ] ( Table 4 ). A recent study reporting the M2 haplotype frequency as high as 23.6% in the Malays (South-East Asia) is supportive to the high world-wide prevalence of this variant [ 32 ]. Notably, in some previous genetic association studies [ 10 14 ], the reported frequency of the M2 haplotype for the control women was lower (5.1%- 8.3%) than the population frequency estimates based on the 1000G project (9.6%- 16.0%) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 96%